Isolasi dan Karakterisasi Senyawa Metabolit Sekunder dari Ekstrak Etil Asetat Daun Salam (Syzygium polyanthum (Wight) Walp) - Norman Ferdinal; Afrizal; Reynol Devryonda (Jurnal Kimia Unand, 2022)
Salam plant (Syzygium polyanthum) is a plant from the Myrtaceae family and the Syzygium genus, which is widely used as a traditional medicine to treat hypertension, ulcers, diarrhea, skin diseases, lower cholesterol, control uric acid levels, and diabetes. This study aims to isolate and characterize secondary metabolites from the ethyl acetate extract of bay leaves. Isolation of secondary metabolites was carried out by column chromatography and characterization with Ultravolet-Visible (UV-Vis) and Fourier Transform Infrared (FTIR) spectrophotometers. The isolated compound is a white solid of 0.0082 g with a melting point of 190-192°C. The results of the identification of the phytochemical profile on the TLC plate with the Liebermen-Burchard (LB) reagent showed that the compound was a triterpenoid group. The results of the UV-Vis spectrum analysis showed maximum absorption at a wavelength of 221 nm indicating the presence of π-π* electron transitions from the unconjugated C=C bond and the results of the FTIR spectrum analysis showed the presence of OH, C-O (alcohol), C=C groups. (alkenes), C-H is aliphatic and geminal dimethyl.